Idiopathic Bilateral Central Giant Cell Granuloma of Jaw- A Case Report and Brief Review of Reported Cases - Nasim, Aarfa; Mohan, Ravi Prakash Sasankoti; Kamarthi, Nagaraju; Wadhwan, Vijay (Journal of Oral Diagnosis, 2017)
Central giant cell granuloma (CGCG) is a benign intraosseous reactive lesion of jaw with diverse clinical and radiological behaviour pattern. It accounts for 7% of neoplastic bone lesion of jaw with 70% occurring in mandible. CGCG was first considered as giant cell tumor mostly found in epiphyseal region of long bone having both aggressive and non- -aggressive pattern. The etiology of the lesion is not defined. Multiple CGCGs of the jaw bones is very rare and, if it occurs, it is usually associated with hyperparathyroidism in majority of the cases. We report an interesting case in which a 33 year old female came with a swelling present on right side of mandible which was asymptomatic. Another swelling was present on left side which was non-evident and asymptomatic. Clinical, radiological and histopathological examination confirmed the lesions as central giant cell granuloma. Biochemical examination showed no signs of hyperparathyroidism. This report represents a very rare entity in which there is idiopathic bilateral CGCG having both aggressive and non-aggressive type of lesion.